2009
DOI: 10.1124/jpet.109.157909
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Binding Site Occupancy by the Novel GABAA Receptor Subtype-Selective Drug 7-(1,1-Dimethylethyl)-6-(2-ethyl-2H-1,2,4-triazol-3-ylmethoxy)-3-(2-fluorophenyl)-1,2,4-triazolo[4,3-b]pyridazine (TPA023) in Rats, Primates, and Humans

Abstract: The GABA A receptor ␣2/␣3 subtype-selective compound 7-(1,1-dimethylethyl)-6-(2-ethyl-2H-1,2,4-triazol-3-ylmethoxy)-3-(2-fluorophenyl)-1,2,4-triazolo [4,3-b]pyridazine (TPA023; also known as MK-0777) is a triazolopyridazine that has similar, subnanomolar affinity for the benzodiazepine binding site of ␣1-, ␣2-, ␣3-, and ␣5-containing GABA A receptors and has partial agonist efficacy at the ␣2 and ␣3 but not the ␣1 or ␣5 subtypes. The purpose of the present study was to define the relationship between plasma TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 38 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…In order to fully interpret and compare the data generated with the two compounds used, we first determined the brain GABA A receptor occupancy of both L-838,417 and TPA023 and correlated this to nonprotein bound plasma drug levels (Figure 1). In terms of Occ50 values, TPA023 was approximately 0.3 mg/kg and L-838,417 was approximately 1 mg/kg, these data are very similar to those published by Merck [21, 22]. However, as equivalent doses did not always result in equivalent plasma exposures, in subsequent studies plasma samples were always taken for PK analysis and drug levels correlated to brain GABA A    receptor RO values determined from the results described above.…”
Section: Resultssupporting
confidence: 83%
“…In order to fully interpret and compare the data generated with the two compounds used, we first determined the brain GABA A receptor occupancy of both L-838,417 and TPA023 and correlated this to nonprotein bound plasma drug levels (Figure 1). In terms of Occ50 values, TPA023 was approximately 0.3 mg/kg and L-838,417 was approximately 1 mg/kg, these data are very similar to those published by Merck [21, 22]. However, as equivalent doses did not always result in equivalent plasma exposures, in subsequent studies plasma samples were always taken for PK analysis and drug levels correlated to brain GABA A    receptor RO values determined from the results described above.…”
Section: Resultssupporting
confidence: 83%
“…MK-0777 is a GABA-A α2/α3 partial agonist, with little activity at α1 and α5 subunits, and was developed as a possible treatment for GAD devoid of anxiolytic or amnestic effects. No anxiolytic data from patients with GAD have been published, however a recent PET study in healthy volunteers reported that MK-0777 2mg produced 50-60% occupancy of central benzodiazepine receptors, without producing sedative effects [37]. Given that nonselective full agonist benzodiazepines produce sedation at <30% occupancy, these findings are consistent with a potentially improved tolerability profile for α2/α3 subtype selective ligands.…”
Section: Drugs Interacting With Inhibitory Amino Acid Systemssupporting
confidence: 51%
“…In contrast, at anxiolytic doses of non-selective positive allosteric modulators acting at the BZ site (diazepam, clonazepam, alprazolam, midazolam, lorazepam), significant drowsiness has been associated with low receptor occupancy, ranging from 2 to 30% (Shinotoh et al 1989; Pauli et al 1991; Sybirska et al 1993; Malizia et al 1996; Lingford-Hudges et al 2005). More recently, for the partial GABA A receptor agonists MRK-409 and TPA023, sedation has been reported at a broad range of receptor occupancy, from severe sedation at <10% occupancy (MRK-409) or lack of overt sedation up to 50% receptor occupancy (TPA023) (Atack et al 2010, 2011a,b). One possible explanation for this broad range of tolerated levels of GABA A receptor occupancy of novel partial GABA A receptor agonists may be their intrinsic activity as suggested in the early studies comparing GABA A receptor modulators (Bottlaender et al 1994).…”
Section: Discussionmentioning
confidence: 99%